IMPLEMENTATION OF POSITIVE PSYCHOLOGY IN IMPROVING THE COMPETENCE OF ASATIDZ AT TPA NITIKAN YOGYAKARTA - Meitya Putri Akase, Eka (International Journal of Multidisciplinary Reseach, 2025)
In improving teacher competence, there are many challenges, one of the efforts that can be offered is positive psychology. Positive psychology is a branch of science that focuses on strengths, advantages, and positive potential in humans. In its application, this positive psychology can be applied in the world of education. So this study aims to examine the effect of the application of positive psychology in improving the competence of asatidz at TPA Nitikan, Yogyakarta. Through a qualitative approach, this study involved observation, in-depth interviews, and document analysis. The results of the study showed that the application of positive psychology had a significant positive impact on increasing motivation, welfare, and teacher competence. More broadly, asatidz become more confident, creative, able to build good cooperation and can create interesting classroom management. This study concludes that positive psychology is an effective approach to improving the quality of Islamic-based Quran education at TPA Nitikan, Yogyakarta.